Economic evaluation of reopening a dormant tree improvement programme: a case study with Scots pine in Scotland - Saraev, Vadim; Ahtikoski, Anssi; Whittet, Richard; Ray, Duncan (Oxford University Press, 2024)
The deployment of improved forest reproductive material (FRM) selected to yield greater timber volume and quality than unimproved material could help to maintain productive, sustainable, and resilient forests and increase resistance to abiotic and biotic threats under extreme climate change events. In Scotland, Scots pine (Pinus sylvestris L.) is a productive species that aligns with these objectives. However, confidence in Scots pine has been low in recent years due to damage caused by the needle blight Dothistroma septosporum. Recent provenance/progeny trials using native Scots pine material from the Caledonian pine woods indicate a favourable genetic correlation between growth and resistance to D. septosporum, suggesting that simultaneous improvements are possible. The Scots pine breeding programme in Scotland was closed in 2002. Here, we present an economic case for reopening the breeding programme to further improve Scots pine FRM. Specifically, we evaluate the costs and potential benefits of supporting a new programme. We conduct an analysis using three improvement scenarios using a Faustmann formula (amended with thinnings) to maximize the land expectation value. Our results indicate that further improvement of Scots pine FRM would be cost-effective, outperforming the current Scots pine timber production and financial outcomes. The analysis shows that the Central scenario’s land expectation value rises by £883 ha−1 compared to the baseline of £79 ha−1, assuming a 3.5% interest rate. We employed both annuity calculations and a break-even analysis to show improved FRM could maintain a breeding programme investment of £3.5 million per year over a 30-year period with a break-even cost threshold increase of ~52% for purchasing improved planting materials from £0.33 to £0.50 per seedling. In conclusion, the study provides economic evidence of the commercial benefits for reopening the Scots pine breeding programme to increase timber production and financial returns.
Keywords: tree breeding; economics; Scots pine; optimisation